The evidence-based medicine pico strategy applied to dentistry using Mesh, Emtree and Decs - Alarcón-Gil, María Teresa; Osorio-Toro, Sonia; Baena-Caldas, Gloria Patricia (Revista Facultad de Odontología Universidad de Antioquia, 2019)
Introduction: the PICO mnemonic is an evidence-based medicine tool that helps formulate the research questions needed to conduct the right search for scientific information. To properly classify this information, controlled languages or thesauruses are used for information retrieval. The aim was to identify whether the PICO search strategy in evidence-based medicine using the MeSH, Emtree and DeCS thesauruses answers a research question in the field of dentistry. Methods: to carry out the PICO strategy, a research question was formulated, identifying the natural language terms for each component of the PICO acronym, which were normalized into the three thesauruses to create the search equations. Results: 43 results were found on Medline through PubMed, 5 on Embase, and 0 on LILACS. There were 4 original articles that answer the research question, proving to be an effective strategy for finding clinical evidence. Conclusion: this study shows that the strategy helps obtain results to answer the question posed. It should be noted that, in order to successfully search and retrieve information, researchers should use the PICO strategy and get familiar with the thesauruses that help structure search equations in the various bibliographic databases.